Advances in accounting behavioral research. Vol. 25 - Karim, Khondkar E., 1961- (Emerald Publishing Limited, 2022)
Focusing on research that examines both individual and organizational behavior relative to accounting, Volume 25 of Advances in Accounting Behavioral Research uncovers emerging theories, methods and applications. From the dark triad, ethical fading, and ethicality of behavior to the effects of CSR reputation and crisis response strategy on investor judgements, the authors compile innovative and new explorations into the behavioral aspects of accounting and audit. Working on both the individual and organizational level, this collection is essential reading for accounting students and educators, providing a unique, interdisciplinary forum with valuable insights on practice for those working in the field. Advances in Accounting Behavioral Research promotes research across all areas of accounting, incorporating theory from, and contributing knowledge to, the fields of applied psychology, sociology, management science, ethics and economics.
Keywords: Accounting.; Economics -- Psychological aspects.; Business & Economics -- Accounting -- General.; elektronické knihy; electronic books